MEASURING THE DARK MATTER CONTENT OF DWARF SPHEROIDAL GALAXIES - Saturni, Francesco G.; Doro, Michele; Nakashima, Kaori; Morselli, Aldo; Rodríguez-Fernández, Gonzalo (Frascati Physics Series, 2022)
Dark matter, a large (∼85%) non-baryonic and non-relativistic component of the matter density of the Universe, likely consists of one or several so-far undetected particles hypothesized in theories beyond the Standard Model. One of the most promising approaches to shed light on the nature of dark matter particles is to search for signatures of their annihilation or decay into Standard Model particles from regions of the sky believed to be highly dark-matter dominated, such as the Galactic Center, the clusters of galaxies and the dwarf spheroidal galaxies around the Milky Way. In this context, dwarf spheroidal galaxies are among the most promising observational targets due to their relative proximity and lack of astrophysical background sources. In this contribution, we present new determinations of the dark matter amount (i.e. the astrophysical factors for dark matter annihilation and decay) in dwarf spheroidal galaxies halos obtained through a Monte-Carlo Jeans analysis of their brightness and kinematic data. We also discuss the systematic uncertainties affecting the calculation of such quantities.
CRIS-Team Scopus Importer:2024-12-16